Compact and high isolation microstrip diplexer for GPS and UWB application. Issue 10 (1st May 2013) - Deng, H.W.; Zhao, Y.J.; Fu, F.; Zhou, X.J.; Liu, Y.Y.
Abstract : A novel microstrip diplexer with low insertion loss, high selectivity and isolation performance is proposed through the combination of two compact filters composed of short‐circuit centred stepped impedance resonators and, a side‐coupled shorted microstrip line, which are designed for GPS and UWB application, respectively. Due to the intrinsic characteristics and mutual loading effect of the two filters, multiple transmission zeros can be created to improve the out‐of‐band rejection and isolation of the diplexer. More compact size is obtained without an extra junction matching networks. Simulated results of the fabricated diplexer agree well with measured ones.